The selection of police pursuits of fleeing motorists for coverage in newspapers - Briggs, Steven J. (Journal of crime and justice, 2018)
The selection process that determines which police-public interactions are considered newsworthy and result in coverage has rarely been examined. Given the potential impact on public understanding, it is important to understand what factors lead some interactions to receive coverage in local news media outlets. This study uses official reports of pursuits of fleeing motorists collected from police departments within the Minneapolis/St. Paul area and matches these events to articles from the largest daily newspapers in the region to examine which pursuit characteristics are associated measures of newsworthiness. Findings reveal pursuits involving the injury or fatality of officers, fleeing motorists, or third parties are disproportionately selected for coverage and have more articles written per pursuit. Implications for public perceptions, policy-makers, and researchers are discussed.